Effect of Alkyl Chain Length on Current‐Voltage Characteristics of BODIPY Molecules Deposited on Si(n++) Substrates. Issue 45 (5th December 2022) - Shivran, Neelam; Koiry, Shankar P.; Kushwah, Nisha; Chauhan, Anil K.; Aswal, Dinesh K.; Chattopadhyay, Subrata; Mula, Soumyaditya
Abstract: Despite having good electronic properties, BODIPY (boron dipyrromethene) and its derivatives attract less research attention towards the development of BODIPY based molecular electronics. Here we have investigated the effect of alkyl chain length attached to BODIPY molecule on its diode and negative differential behaviour. An undecenyl‐BODIPY dye (BODIPY‐C11) was designed, synthesized and deposited on Si (111) surface which was further converted into a bilayer using another BODIPY dye, PM567. Various techniques were used to check the arrangement and thickness of the layers which established that the designed molecule is suitable for compact grafting on Si surface. Electrical behaviour of BODIPY‐C11 monolayer and bilayer showed rectification (rectification ratio=500) and NDR property (peak‐to‐valley ratio=1000), respectively with improved device performances as compared to the electrical characteristics shown by 2, 6‐diethyl‐4, 4‐difluoro‐1, 3, 5, 7‐tetramethyl‐8‐(4'‐(4"‐penteneoxyphenyl)‐4‐bora‐3a, 4a‐diaza‐ s ‐indecene (BODIPY‐C5) grafted on Si. This study established that the electrical behaviour of BODIPY can be modulated by simply changing the alkyl chain length, which will be useful for the development of BODIPY‐based electronic materials. Abstract : Charge transport properties of BODIPY layers grafted on Si(n ++ ) Substrates are efficiently modulated by changing the attached alkyl chain length as well as by bilayer formation. BODIPY‐C11 monolayer and bilayer showed rectification (RR=500) and NDR property (PVR=1000) respectively with improved device performances as compared to monolayer and bilayer of BODIPY‐C5 grafted on Si(n ++ ).